Revisit the Dynamic Portfolio Formation between Gold and Stocks in Indonesia in the Period Before and During the COVID-19 Pandemic - Ashalia Fitri Yuliana; Robiyanto Robiyanto (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
This research aims to review the formation of the dynamic portfolio of individual stocks and gold using the DCC-GARCH and ADCC-GARCH analysis techniques in the periods before and during the COVID-19 pandemic. This is done so that individual investors and investment managers will be able to apply this method. This research uses data from the period of October 2019 - September 2020 with a research sample of nine stocks that are included in the IDX-30. The results showed that the DCC-GARCH analysis technique before the COVID-19 pandemic and the performance of the dynamic portfolios that were unhedged and hedged had nodifference. This is due to the conditions in the period before the COVID-19 pandemic which still tended to be stable, thus, no safe-haven asset is needed. Meanwhile, in the period during the COVID-19 pandemic, using the DCC-GARCH analysis technique, there were differences because conditions started to fluctuate in uncertainty which resulted in the need for safe-haven assets. On the other hand, using the ADCC-GARCH analysis technique on the periods before and during the COVID-19 pandemic, the performance of the dynamic portfolios that were unhedged and hedged showed a difference. Because the ADCC-GARCH technique is able to see asymmetric volatility for the future, adding gold to a portfolio can reduce risk when there is uncertainty. This research also found that the ADCC-GARCH technique had better performance than the DCC-GARCH technique.